Financial Distress Moderates the Effect of KAP Reputation, Auditor Switching, and Leverage on the Acceptance of Going Concern Opinions - Laksmita, Briliani; Sukirman, Sukirman (Accounting Analysis Journal, 2020)
This research intended to measure the influence of reputation of public accounting firm, auditor switching and leverage against the acceptance of going concern opinion with financial distress as a moderating variable. This study used manufacturing companies that listed on the Indonesia Stock Exchange (IDX) in 2015-2018 as population. The sample selection used purposive sampling and obtained 100 units of analysis. Data analysis method used logistic regression and interaction test with IBM SPSS 24 tools. The study showed that auditor switching had a positive influence on going concern opinion. Meanwhile, the reputation of the public accounting firm and leverage had no effect on going concern opinion. In addition, the results of the study showed that financial distress strengthened the effect of leverage on going concern opinion. However, financial distress was unable to moderate the influence of the reputation of the public accounting firm and auditor switching towards the acceptance of going concern opinion. The conclusion of this study is companies that change its auditor will most likely receive going concern opinion if company’s continuity is disrupted, all Public Accounting Firms attempt to work independently and objectively, and leverage has different effect on every company. Distressed companies will most likely receive going concern opinion if they have high leverage ratio. Keywords: Going Concern Opinion; Non-Financial Factors; Financial Condition